Determining patterns of lactose hydrolysis in liquid concentrates of demineralized whey - Mykhalevych, Artur; Moiseyeva, Lydmila; Polishchuk, Galyna; Bandura, Uliana (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study was the process of milk sugar hydrolysis in liquid whey concentrates. The problem solved was the intensification of the lactose hydrolysis reaction in liquid whey concentrates through the use of a combination of leavening and enzyme preparations. Patterns in the lactose hydrolysis process in liquid concentrates of demineralized whey were studied. It was established that the use of an enzyme preparation for liquid whey concentrates does not make it possible to achieve a degree of lactose hydrolysis higher than 75–77 % within 10 h. The simultaneous use of enzyme and leavening preparations for 6 hours ensures the conversion of more than 95 % of lactose for concentrates with a mass fraction of dry substances of 10–30 % and more than 90 % for a 40 % concentrate. The rational duration of lactose hydrolysis in demineralized whey concentrates for the combination of preparations is 6 hours for 10 and 20 % concentrates, and 8 h for 30 and 40 % concentrates, which enables lactose hydrolysis at the level of 96.8–100 %. The rheological properties of concentrates with a solids content of 30 and 40 % indicate that these systems have a high ability to restore the structure. The dynamics of monosaccharide formation during hydrolysis are similar for 10 and 20 % concentrates, in which galactose slightly predominates the systems. Data on the increase in glucose content in fermented 30 and 40 % concentrates contradict the known data regarding the consumption of glucose by the acidophilic bacillus and its conversion to galactose. This may indicate suppression of the activity of the acidophilic bacillus under conditions of increased osmotic pressure in the concentrates. The results of the work could be used in the technology of whey ice cream, as well as dairy products that require adjustment of the chemical composition, primarily in terms of protein and lactose content